Functional HLA-DM on the surface of B cells and immature dendritic cells - Arndt, Sven O.; Moldenhauer, Gerhard; Sun, Yuansheng; Schadendorf, Dirk; Hämmerling, Günter J.; Kropshofer, Harald (The EMBO journal, 2000)
HLA-DM (DM) plays a critical role in antigen presentation through major histocompatibility complex (MHC) class II molecules. DM functions as a molecular chaperone by keeping class II molecules competent for antigenic peptide loading and serves as an editor by favoring presentation of high-stability peptides. Until now, DM has been thought to exert these activities only in late endosomal/lysosomal compartments of antigen-presenting cells. Here we show that a subset of DM resides at the cell surface of B cells and immature dendritic cells. Surface DM engages in complexes with putatively empty class II molecules and controls presentation of those antigens that rely on loading on the cell surface or in early endosomal recycling compartments. For example, epitopes derived from myelin basic protein that are implicated in the autoimmune disease multiple sclerosis are down-modulated by DM, but are presented in the absence of DM. Thus, this novel concept of functional DM on the surface may be relevant to both protective immune responses and autoimmunity.
Gesehen am 22.02.2019